Pengembangan Strategi Pembelajaran Berbasis Keteladanan untuk Meningkatkan Karakter Disiplin pada Anak di SDN 24 Kota Bengkulu - Lilik Lestari; Indayu Adriansi; Alia Idnin Amanda; Selly Nopriani; Rati Diana Sari; Pelangi Pandu Pratiwi (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program was carried out to improve students’ disciplinary character through the implementation of role-model-based learning strategies at SDN 24 Bengkulu City. Initial observations indicated low levels of discipline in students’ daily activities, such as lack of orderliness during classroom learning, untidy behavior during meal sessions, inconsistency during scout marching activities, and limited discipline during flag ceremonies. To address these issues, the program involved direct observation, teacher counseling, training sessions, and mentoring that emphasized consistent role modeling across various school activities. Data were collected using naturalistic observation and photographic documentation throughout the program. The results showed noticeable improvements in students’ discipline, reflected in better learning readiness, more orderly conduct during meal times, increased accuracy in following marching commands, and improved respectful behavior during ceremonies. These changes emerged gradually as teachers demonstrated consistent exemplary behavior. The program concludes that role-model-based learning strategies are effective for fostering discipline in elementary school students and can be sustainably implemented.